THE EFFECT OF THE FERTILIZERS ON PHOTOSYNTHETIC ACTIVITY OF SPRING WHEAT SOWINGS IN THE VARIOUS AGROLANDSCAPE CONDITIONS - L. I. Petrova; A. E. Artemiev; N. K. Pervushina; V. N. Lapushkina (Зерновое хозяйство России)
The article considers the results of three-year trials carried out on the experimental plots of All-Russian Research Institute of Meliorated Lands (ARRIML). On the plots located on the drained sod-podzolic soils of various mechanic composition, there was studied the features of formation of the indexes of photosynthetic ability of spring wheat in the various agrolandscape conditions. The article presents the dependence of the indexes of water-air regime of the arable soil layer, assimilative activity of spring wheat sowings, the value of its productivity due to the studied factors. The best conditions of the moisture supply of the arable soil layer have been created on the medium loamy gley soils of the northern slope in contradiction to the slightly loamy gley soils of the flat top and the sand-loamy weak gley soils of the southern slope. The increase of the amount of the fertilizers for the spring wheat in all agromicrolandscapes gave positive effect on the formation of suitable surface. The use of the combination of 12 t/ha of multi-purpose compost and N60 Р60 К60 turned to be the most efficient on the slopes. Not only the leaf area, but also the total photosynthetic capacity of spring wheat sowings increased due to the increasing of fertilizing, especially on the slopes. According to the experimental results, the use of 2.89 t/ha of multi-purpose compost on the medium loamy gley soils of the northern slope, 2.32 t/ha of multi-purpose compost on the slightly loamy gley soils of the flat top and 2.59 t/ha of multi-purpose compost with N60 Р60 К60on the sand-loamy weak gley soils of the southern slope produced the best yields of spring wheat. It’s necessary to mention that in the variants of high level of fertilizing on the northern slope and on the flat top there has been a lodging of plants that reduced the productivity.